Super-Tough and Environmentally Stable Aramid. Nanofiber@MXene Coaxial Fibers with Outstanding Electromagnetic Interference Shielding Efficiency - Liu-Xin Liu; Wei Chen; Hao-Bin Zhang; Lvxuan Ye; Zhenguo Wang; Yu Zhang; Peng Min; Zhong-Zhen Yu (Nano-Micro Letters, 2022)
Abstract Although electrically conductive and hydrophilic MXene sheets are promising for multifunctional fibers and electronic textiles, it is still a challenge to simultaneously enhance both conductivity and mechanical properties of MXene fibers because of the high rigidity of MXene sheets and insufficient inter-sheet interactions. Herein, we demonstrate a core–shell wet-spinning methodology for fabricating highly conductive, super-tough, ultra-strong, and environmentally stable Ti3C2T x MXene-based core–shell fibers with conductive MXene cores and tough aramid nanofiber (ANF) shells. The highly orientated and low-defect structure endows the ANF@MXene core–shell fiber with super-toughness of ~ 48.1 MJ m−3, high strength of ~ 502.9 MPa, and high conductivity of ~ 3.0 × 105 S m−1. The super-tough and conductive ANF@MXene fibers can be woven into textiles, exhibiting an excellent electromagnetic interference (EMI) shielding efficiency of 83.4 dB at a small thickness of 213 μm. Importantly, the protection of the ANF shells provides the fibers with satisfactory cyclic stability under dynamic stretching and bending, and excellent resistance to acid, alkali, seawater, cryogenic and high temperatures, and fire. The oxidation resistance of the fibers is demonstrated by their well-maintained EMI shielding performances. The multifunctional core–shell fibers would be highly promising in the fields of EMI shielding textiles, wearable electronics and aerospace.